Palyatif Bakım Ünitemizde Yatan Hastaların Retrospektif Analizi - Ökkeş Hakan Miniksar; Ahmet Aydın (Journal of Contemporary Medicine, 2020)
AbstractObjectives: In this study, we aimed to investigate the clinical and demographic characteristics of patients hospitalized in the Palliative Care Center (PBM) of our hospital and to investigate the factors associated with discharge status and compare them with the literature.Materials and Methods: In this retrospective study, data were obtained by examining the file records of the patients who were followed up and treated in the Hospital Information Management System and archives of Malatya Training and Research Hospital PBM between June 2016 and April 2018.Results: The mean age of the 321 patients (53.9% male, 46.1% female) included in the study was 72.5 ± 14.7 and the mean length of hospitalization was 15.4 ± 23.2 (1-275) days. The most frequent outpatients (37.4%), intensive care unit (27.8%), wards (23.1%) and emergency department (11.6%) were found to be the most frequently referred patients. The most frequent hospitalization indications were inadequate oral intake (general disorder), 58.3%, care training 14.3%, pain palliation 12.8% and decubitus wound care 7.5%. The most common comorbidities were SVO, Alzheimer's disease, HT, COPD, and DM, respectively. It was found that 139 (43.3%) of the patients were hospitalized due to malignancy and the most common type of malignancy was lung cancer and later gastric cancer. As the discharge status; 42.7% of the patients were discharged home, 8.7% were transferred to the 3rd Stage Intensive Care Unit, 6.9% were discharged voluntarily, 3.7% were transferred towards, 1.2% were advanced and 36.8% of the patients were ex. It was observed that approximately half (74) of 139 patients with malignancy were mortal and 4 patients were transferred to intensive care unit. Long hospitalization period (longer than 1 month) was seen in patients hospitalized for decubitus wound care (29.1%) and care education (13%).